Differential regulation of skeletal stem/progenitor cells in distinct skeletal compartments - Solidum, Jea Giezl Niedo; Jeong, Youngjae; Heralde, Francisco; Park, Dongsu (Frontiers in Physiology, 2023)
Skeletal stem/progenitor cells (SSPCs), characterized by self-renewal and multipotency, are essential for skeletal development, bone remodeling, and bone repair. These cells have traditionally been known to reside within the bone marrow, but recent studies have identified the presence of distinct SSPC populations in other skeletal compartments such as the growth plate, periosteum, and calvarial sutures. Differences in the cellular and matrix environment of distinct SSPC populations are believed to regulate their stemness and to direct their roles at different stages of development, homeostasis, and regeneration; differences in embryonic origin and adjacent tissue structures also affect SSPC regulation. As these SSPC niches are dynamic and highly specialized, changes under stress conditions and with aging can alter the cellular composition and molecular mechanisms in place, contributing to the dysregulation of local SSPCs and their activity in bone regeneration. Therefore, a better understanding of the different regulatory mechanisms for the distinct SSPCs in each skeletal compartment, and in different conditions, could provide answers to the existing knowledge gap and the impetus for realizing their potential in this biological and medical space. Here, we summarize the current scientific advances made in the study of the differential regulation pathways for distinct SSPCs in different bone compartments. We also discuss the physical, biological, and molecular factors that affect each skeletal compartment niche. Lastly, we look into how aging influences the regenerative capacity of SSPCs. Understanding these regulatory differences can open new avenues for the discovery of novel treatment approaches for calvarial or long bone repair.